Integrating ESG, Sustainability Strategy, and Firm Value: A Systematic Literature Review and Conceptual Framework - Martini Martini; I Gusti Ketut Agung Ulupui; Adam Zakaria (Poltanesa, 2026)
Through a Systematic Literature Review (SLR) guided by PRISMA 2020 protocols, this paper maps out and assesses the scattered research surrounding Environmental, Social, and Governance (ESG), sustainability frameworks, and overall corporate worth. We gathered data from Web of Science and Scopus using targeted Boolean strings, landing on 55 peer-reviewed papers spanning 2015 to 2024 after rigorous screening. The collected data shows that while ESG actions and disclosures serve as vital outward signals that boost corporate transparency and stakeholder confidence, their direct impact on market value is still heavily debated. Instead, the real value transformation happens inside the company. Internal dynamics specifically deeply rooted sustainability strategies, solid governance structures, and core institutional strengths act as the true engines that turn ESG efforts into tangible economic gains.